Understanding obesity in children with 22q11.2 deletion syndrome - Sarli, Walter Maria; Cerutti, Matteo; Pontone, Matteo; Guarnieri, Valentina; Soldovieri, Sara; Giotta, Massimo; Ricci, Silvia; Azzari, Chiara; Stagi, Stefano (Frontiers in Endocrinology, 2025)
Background22q11.2 deletion syndrome (22q11.2DS) is a complex and heterogeneous genetic disorder. While short stature is well-documented, data on weight excess in pediatric patients remain sparse and conflicting.ObjectiveTo evaluate the prevalence of overweight and obesity in children and adolescents with 22q11.2DS when compared to the general Italian pediatric population and identify risk factors and periods of critical weight gain.MethodsIn this single-center, retrospective study, 61 children with molecularly confirmed 22q11.2DS were followed up for 441 patient-years. Anthropometric data were evaluated and compared to national surveillance databases (“OKKio alla Salute” and “HBSC”). Risk factors for overweight and obesity were identified by univariate and multivariate analyses.ResultsWhile overweight prevalence in 22q11.2DS patients did not differ significantly from that in the general population, obesity had a bimodal age distribution with peaks at 11 and 17 years. Both neuropsychiatric comorbidities and the use of psychoactive medication were significantly associated with an increased risk of overweight and obesity. In multivariate analysis, the use of psychoactive medication was the only independent risk factor.ConclusionsObesity in 22q11.2DS may not be syndrome-intrinsic but is heavily influenced by pharmacological treatment. Identification of vulnerable periods and modifiable risk factors is crucial. A preventive, multidisciplinary approach with metabolic screening and cautious use of psychotropic medication is warranted to avoid obesity risk in this population.